2019
DOI: 10.1007/s10488-019-00925-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Youth Improvement in Community-Based Residential Settings with Practices Derived from the Evidence-Base

Abstract: Several of these committee members met with me on multiple occasions to teach me new statistical procedures and ensure that this dissertation was scientifically valid and completed to the best of my abilities. I want to especially thank Dr. Brad Nakamura, my advisor, for his dedication in my development as a scientist. Dr. Nakamura's support, encouragement, and motivation greatly influenced the progress and completion of this dissertation.My sincerest thanks are also given to Hilary Gould, Kaitlin Hill, Priya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…Further, studies should continue to explore novel service modalities for rural families, such as telehealth, and ways to build rural workforce capacity, such as Project ECHO (Extension for Community Healthcare Outcomes; https://hsc.unm.edu/echo/). The finding that both individual and family interventions are significant predictors of youth outcomes, the "multiple PE use approach," is consistent with prior community care research (e.g., Izmirian et al, 2019) and indicates future work is still needed to determine what works for whom and under what constraints. It is imperative that future studies examine community care within geographically isolated settings, to close the gap between research and practice, and improve dissemination and implementation efforts for these residents.…”
Section: Hee and Muellersupporting
confidence: 71%
See 1 more Smart Citation
“…Further, studies should continue to explore novel service modalities for rural families, such as telehealth, and ways to build rural workforce capacity, such as Project ECHO (Extension for Community Healthcare Outcomes; https://hsc.unm.edu/echo/). The finding that both individual and family interventions are significant predictors of youth outcomes, the "multiple PE use approach," is consistent with prior community care research (e.g., Izmirian et al, 2019) and indicates future work is still needed to determine what works for whom and under what constraints. It is imperative that future studies examine community care within geographically isolated settings, to close the gap between research and practice, and improve dissemination and implementation efforts for these residents.…”
Section: Hee and Muellersupporting
confidence: 71%
“…Despite a large amount of variance occurring on the therapist level, this study found that none of the available therapist variables were significant predictors of improvement. Previous research examining these therapist variables (i.e., professional specialty, degree, licensure status) found similar nonsignificant predictors in the context of significant variance at this level of the model (Izmirian et al, 2019;Wilkie et al, 2018). Other therapist variables might be related to substance use treatment progress, such as theoretical orientation, prior training in and fidelity of evidencebased practices, and the ability to develop an effective therapeutic alliance.…”
Section: Discussionmentioning
confidence: 77%